The formation of optimal stocks portfolio using Markowitz, single index, and Capital Asset Pricing Models on LQ45 Index of 2016-2020 period - Angelia, Rahel; Siagian, Jonny; Mangani, Ktut Silvanita (Technium Social Sciences Journal, 2021)
This research aims to create an optimal portfolio using the Markowitz, Single Index, and Capital Asset Pricing Models. The sample consists of 27 LQ45 Stocks Index consistently recorded between 2016 and 2020. According to the study's findings, the optimal portfolio formation of the Markowitz Model consists of 10 stocks (BBCA, UNVR, ICBP, TLKM, GGRM, UNTR, JSMR, ADRO, PTBA, and SRIL) with an expected portfolio return of 1.06 percent per month and portfolio risk of 3.68 percent per month. The optimal portfolio of the Single Index Model consists of six stocks (BBCA, PTBA, ADRO, INCO, UNTR, and ICBP) with a monthly return of 2.16 percent and a portfolio risk of 2.98 percent. Meanwhile, the Capital Asset Pricing Model's optimal portfolio formation consists of seven stocks (BBCA, ICBP, KLBF, UNTR, ADRO, PTBA, and ASII) with an expected monthly portfolio return and portfolio risk of 1.51 and 4.14 percent. Based on portfolio performance evaluations using the Sharpe Ratio, Treynor Ratio, and Jensen's Alpha shows the portfolio performance of the Single Index Model outperforms the Markowitz and Capital Asset Pricing Models. The comparison gives information for the investor when choosing the best portfolio shares of LQ45 based on data in the period of 2016-2020.